L'expérience africaine - Sy, Seydou (Les Cahiers de droit, 1987)
Due to the pressures of economic and social development, certains underdeveloped countries choose to interpret in their own way the texts of the United Nation's Universal Declaration of Human Rights and give only secondary importance to human rights when they are not perceived as an outright hindrance to development. The consideration given to the subject of Human Rights by the Organization of African Unity in 1979 resulted in the adoption of an African Charter (Banjul) on Human and People's Rights in 1981 which constitutes a decisive step in the evolution of the attitude of African countries in regard to the problem of Human Rights. The author examines the characteristics of this Charter and the efforts of Senegal to incorporate the Charter's principles into its internal law. The author uses the example of Senegal to demonstrate that the imperatives of development are compatible with the respect of Human Rights.